Synchronous diffuse large B-cell lymphoma of the stomach and small cell lung carcinoma: A case report. Issue 50 (December 2017) - Li, Jia; Zhou, Changli; Liu, Wanqi; Sun, Xun; Meng, Xiangwei
Abstract: Rationale: The synchronous occurrence of lung cancer in patients with gastric neoplasms is relatively uncommon, especially the cases of synchronous coexistence of small cell lung carcinoma and diffuse large B-cell lymphoma of the stomach. Patient concerns: We encountered a case of synchronous primary small cell lung carcinoma and diffuse large B-cell lymphoma of the stomach. A 63-year-old patient with a 7.5 × 5.09 cm mass in the superior lobe of the right lung diagnosed with small cell lung cancer and synchronous diffuse large B-cell lymphoma of the stomach. Diagnoses: The diseases were diagnosed by the pathological biopsy and immunohistochemical methods. Interventions: As the patient received CHOP chemotherapy, pulmonary function deterioraed. Etoposide was added to the chemotherapy. Outcomes: However, after the first treatment, chest computed tomography showed that the mass in the superior lobe of the right lung had increased to 8.5 × 5.2 cm. Lessons: This report draws attention to the fact that the treatment of synchronous tumors is a challenge.